Mapping Vulnerability of aquifer to saltwater intrusion using fuzzy membership function - Marjan Moazamnia; Sina Sadeghfam; Alireza Babaeian Amini (Journal of Hydraulic Structures)
Groundwater is one of the most important sources of drinking, industrial, and agricultural water in arid and semi-arid regions, where the occurrence of droughts, rapid population growth, and the corresponding increase in water demand threaten groundwater resources. Over-exploitation and mismanagement of groundwater resources result in environmental problems such as subsidence and saltwater intrusion in coastal aquifers. The risk of saltwater intrusion threatens the Urmia aquifer due to the proximity of the aquifer to Lake Urmia and severe groundwater decline. This study evaluates the vulnerability of saltwater intrusion by the GALDIT framework. The results show the conservative vulnerability index with low efficiency, where vulnerable areas are limited to a narrow strip near the coastline. Fuzzy membership functions were employed within the GALDIT framework to increase efficiency. The results of the modified GALDIT resolve the weakness of presenting conservative results in the basic GALDIT framework.